Uso potencial de fitoquímicos derivados de microalgas para la obtención de nutracéuticos (2017)
The objective of this article is to make known the commercial and nutritional benefits that brings the industrial production of bioactive compounds derived from microalgae. According to the literature consulted for this study, these compounds (called phytochemicals) after an isolation and purification process can be marketed as food, that is, foods that help prevent diseases or health risk factors. Although the benefits of chemical products derived from microalgae and their value as nutraceuticals have been proven, research on this topic is not enough. It is concluded that most of the research has been relegated to a laboratory level, since they take these ideas to industrial production requires significant financial support.